Applied Stakeholder Analysis in Mapping Political Actors Involved in the Implementation of Universal Health Care in 25 Provinces in the Philippines - Apostol, Geminn Louis C (Archīum Ateneo, 2021)
IntroductionStakeholder perceptions on health policy reforms are key inputs for evidence-based policy development and implementation (Lavis, 2009; WHO, 1993). To this end, stakeholder analysis (SHA) is a useful tool for gathering insights on stakeholders’ interests in, positions on, and power to influence health policy issues that aim to achieve universal health coverage (UHC). There is little evidence on the use of SHA in health policy development and even less in informing the politics of implementing health system reforms towards UHC. This study demonstrates the utility of SHA as a tool for evidence-based policy development for UHC, drawn from the experience of doing SHA with political actors in 25 provinces involved in the pilot implementation of the recently enacted UHC Law in the Philippines. MethodologyWe used a participatory process to systematically identify political actors with ‘significant influence on decisions, policies, and outcomes’ in relation to the pilot implementation of the UHC Law (Wolsfield, 2015). We used group brainstorming and cognitive interviewing techniques to assess stakeholder perception on five domains: [1] stakeholder interests, [2] position, [3] level of knowledge, [4] degree of power/influence, and [5] capability to mobilize resources to implement the UHC Law. We also tracked changes in stakeholders’ responses to various reform scenarios. We studied qualitative data through thematic analysis. We determined frequencies for categorical responses in each domain and mapped in three-dimensional stakeholder matrices. ResultsAn average of 26 stakeholders for each province were identified (n=642), categorized as: elected local officials (27%, n=173), local health authorities (23%, n=148), local administrators (18%, n=115), healthcare providers (16%, n=103), civil society (12%, n=77), and non-profit organizations (4%, n=26). The majority of political actors agreed on the overall goals and provisions of the UHC Law, especially those in low-income municipalities for whom the law presents opportunities to address financing gaps. Political actors in high-income localities feel that they have less to gain from UHC implementation and more to lose as authority is recentralized, and so are generally less supportive. Differences in socioeconomic context and provincial development roadmaps also generate differences in interests and positions of stakeholders regarding pooling of local funds, delineation of financing roles among agencies and levels of governments, and transfer of administrative power over health human resources. Limited policy knowledge and lack of implementation clarity represent significant barriers to ownership and engagement of local stakeholders and private sector actors. Perceptions of additional financing and administrative burden negatively affect stakeholders’ position on UHC implementation. ConclusionsDifferences in context and localization of UHC policy reforms exert strong influence in the interests of stakeholders and their position on the reforms. While cross-contextual policy comparisons around these specific issues will be difficult, learning is still possible around the approach to analysis, the factors influencing judgements, and implications for and possible approaches to stakeholder and political management. Given the dynamic nature of policy change and the complex nature of UHC reforms, doing SHAs in iteration can offer clearer insights to support policy change towards ensuring the political viability of UHC policy reforms.